PROFIL TITER ANTIBODI Avian influenza (AI) MELALUI UJI Haemaglutination Inhibition (HI) DAN IDENTIFIKASI PENERAPAN BIOSECURITY DI PETERNAKAN AYAM FILIPHINE KOTA GORONTALO - Solang, Margaretha; Hamidun, Sabriyanto; Uno, Wirnangsih D (Universitas Jambi, 2022)
This research aimed to determine the percentage of protective antibody titers of Avian influenza (AI) and the application of biosecurity in Filipino chicken farms in Gorontalo City. This research used direct observation of the application of biosecurity on farms, and data on Avian influenza antibody titers were obtained based on the results of tests conducted during the intership at Class II Agricultural Quarantine Center of Gorontalo. Data analysis was carried out ini a qualitative descriptive manner. The results showed that the percentage of protective antibody titers for Avian influenza (AI) in the 3 Filipino chicken farms was 3.22% in farm ZD, 0% in farm MCY, and 0% in farm AT. The percentage obtained shows that the presence and spread of Avian influenza in the 3 Filipino chicken farms in Gorontalo City is still low. The application of biosecurity on farms shows that the 3 Filipino chicken farms in Gorontalo City were focused on isolation and sanitation, although the implementation was still lacking in detail and comprehensiveness. The focus of biosecurity on isolation and sanitation components causes weaknesses in traffic control components. Keyword: Avian influenza antibody titer, protective antibody, application of biosecurity, Filipino chicken